2019
DOI: 10.1111/cas.13988
|View full text |Cite
|
Sign up to set email alerts
|

Cinobufagin suppresses colorectal cancer angiogenesis by disrupting the endothelial mammalian target of rapamycin/hypoxia‐inducible factor 1α axis

Abstract: Inducing angiogenesis is a hallmark of cancers that sustains tumor growth and metastasis. Neovascularization is a surprisingly early event during the multistage progression of cancer. Cinobufagin, an important bufadienolide originating from Chan Su, has been clinically used to treat cancer in China since the Tang dynasty. Here, we show that cinobufagin suppresses colorectal cancer ( CRC ) growth in vivo by downregulating angiogenesis. The hierarchized neovasculature is significantly decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Cinobufagin was found to induce apoptosis in osteosarcoma cancer cells by suppressing cancer-promoting signaling pathways such as STAT3, Notch and NF-kB, and activating mitochondria-mediated apoptosis pathways [41][42][43][44]. The anti-angiogenic effect of cinobufagin by suppressing the mammalian target of rapamycin (mTOR) and hypoxia-inducible factor-1α (HIF1α) signaling pathways has also been observed in colorectal cancer [45].…”
Section: Discussionmentioning
confidence: 98%
“…Cinobufagin was found to induce apoptosis in osteosarcoma cancer cells by suppressing cancer-promoting signaling pathways such as STAT3, Notch and NF-kB, and activating mitochondria-mediated apoptosis pathways [41][42][43][44]. The anti-angiogenic effect of cinobufagin by suppressing the mammalian target of rapamycin (mTOR) and hypoxia-inducible factor-1α (HIF1α) signaling pathways has also been observed in colorectal cancer [45].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, an increase in the pro-apoptotic factor Bax and the epithelial marker E-cadherin, while a decline in the anti-apoptotic factor Bcl-2 and mesenchymal markers N-cadherin and Vimentin suggested that sh-KDM3A promoted apoptosis while suppressing EMT in CC cells in a cellular perspective. In addition, angiogenesis, a hallmark of cancers that is crucial for tumor growth and metastasis, 26 was found to be suppressed as well upon KDM3A downregulation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 102 ] In addition, cinobufagin could suppress tumor neovascularization by disrupting the endothelial mammalian target of rapamycin/hypoxia‐inducible factor‐1α (mTOR/HIF‐1α) pathway to trigger ROS‐mediated vascular endothelial cell apoptosis. [ 103 ]…”
Section: The Anticancer Activities Of Toad Venommentioning
confidence: 99%